Simulation of an evacuation system in an urban community with residents and vehicles - Lim, Chuan Jie (Nanyang Technological University, 2023)
Disasters can happen at any time, they can be cause damage to infrastructure, and also be deadly which can break apart families and cause disruption to the daily lives of everyone. Having a well-developed evacuation strategy that minimizes the evacuation time essentially means helping to reduce to number of lives lost. This project therefore looks to improve on current existing evacuation strategies so that the maximum number of people can be evacuated during a disaster, in the minimum amount of time. The existing works that are being looked at uses mathematical models for evacuation planning. Therefore, coding will be used in this project to simulate the effectiveness of existing works and the improved evacuation model. To help facilitate this task, Python is the chosen coding language, while the software used will be Spyder, an open-source cross-platform IDE.